Leaf endophytes and Populus genotype affect severity of damage from the necrotrophic leaf pathogen, Drepanopeziza populi. Issue 10 (24th October 2013) - Busby, Posy E.; Zimmerman, Naupaka; Weston, David J.; Jawdy, Sara S.; Houbraken, Jos; Newcombe, George
Abstract : Fungal leaf endophytes—nonpathogenic microfungi that live within plant leaves—are ubiquitous in land plants. Leaf endophytes and host plant genotypes may interact to determine plant disease severity. In a greenhouse inoculation experiment, we found that leaf endophyte species and Populus angustifolia genotypes both affected disease outcomes in plants inoculated with the necrotrophic leaf pathogen Drepanopeziza populi . Contrary to many studies showing endophytes conferring defense, all plant genotypes inoculated with the endophyte Penicillium sp. prior to inoculation with the pathogen D. populi were characterized by greater pathogen symptom severity than plants inoculated with the pathogen only. We quantified defense gene expression via qRT–PCR, but found no evidence that increased pathogen damage was related to differential expression of the assayed genes. A second endophyte, Truncatella angustata, which was previously found to reduce symptom severity of the biotrophic pathogen Melampsora in Populus trichocarpa, did not affect symptom severity of the necrotrophic pathogen D. populi or defense gene expression. Overall, our study highlights the variable effects of endophytes on pathogen symptom severity, and illustrates that plant genotypic variation can remain important for disease outcomes even in the presence of endophytes altering disease. Additional work is needed to elucidate the mechanism by which fungal leaf endophytes alter disease in their host plants.